Kopciuszek idzie na wojnę? Fallocentryzm a pseudofeminizm w baśniowej dystopii (na przykładzie Cinderella Is Dead Kalynn Bayron) - Matuszko, Kinga (Paidia i Literatura, 2024)
The article analyzes pseudo-feminist ways of creating female characters and the world presented in the novel Cinderella Is Dead (2022) by Kalynn Bayron, which is a reinterpretation of Cinderella. By transforming a known history, the authoress wants to participate in discourses calling for inclusiveness and equality of worldviews. To do so, she introduces various refractions: emphasizes women’s agency and their pursuit of self-determination, and changes the protagonist’s skin color and sexual orientation. She exposes features commonly associated with feminism, which often has the opposite effect, and the work itself can be interpreted as pseudo-feminist. This is particularly visible in measures such as demonizing men or the lack of positive male figures, as well as superficial and instrumental treatment of issues important to feminism. Attention was also paid to the phenomenon of blackwashing, which in the novel is primarily a marketing trick and an expression of cultural fashion.